Non-dialectical Heterogeneity in Costa Rican literaure; selection of three poems of “pezeteña” literature, (1982-1983) - Badilla Fallas, Grettel (2022)
This article presents a study of three national poems with authors from Perez Zeledon. The authors exhibit topics as migration and cultural subjects that miss their origins and traditions meanwhile they live in a constant social and geographic change. Based on the above premise, the main objective of this work is to analyze the stream of non-dialectical heterogeneity in literature from Perez Zeledon, specifically in the poems “A photo to my town” from the author Marcos Valverde (1982), “Mary in New York” from Walter Leiva and “San Jose” from the author Iris Valverde (1983). The poems previously mentioned show the important role of migration in the formation of peripheral societies as well as the affectation that they expose in cultural and economic spheres of Costa Rica.